2021
DOI: 10.1021/acsanm.1c02152
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Construction of Silica Nanotubes Loaded with Pd Nanoparticles for Catalytic Hydrodechlorination of Chlorophenols

Abstract: In this study, we for the first time use ditopic bis-terpyridine-containing metallopolymers as templates to synthesize metal nanoparticle-encapsulated nanoreactors. In the presence of the surfactant cetyltrimethylammonium bromide, the ditopic bis-terpyridines coordinate Pd 2+ ions to form linear metallopolymer bundles, which are further used as templates for silica deposition to give silicified Pd ion-containing tubular metallopolymers. The following calcination and subsequent reduction simultaneously result i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Furthermore, the morphology of the catalyst is particularly important which is essential to influence the energy consumption and kinetic constant of adsorption/desorption behaviors during the HDC process. Using SiO 2 -supported Pd with different structures such as nanotubes and nanoparticles to address 1,2-dichloroethane and chlorophenols, some studies have reported that the reaction activation energy against the dechlorination energy barrier has been improved, and reaction conditions such as the temperature of the hydrogen reduction process can be adjusted to a lower level. , Similar to the gas–solid reaction process, the surface acidity of the catalyst is particularly important for the adsorption of target chlorinated organic compounds in a liquid HDC process. The catalytic system using acid zeolite as the carrier seems to have a high reaction rate because its Brønsted acidity shows high selective adsorption for C–Cl bonds, especially for chlorophenol species …”
Section: Application Of Liquid Phase Dechlorinationmentioning
confidence: 99%
“…Furthermore, the morphology of the catalyst is particularly important which is essential to influence the energy consumption and kinetic constant of adsorption/desorption behaviors during the HDC process. Using SiO 2 -supported Pd with different structures such as nanotubes and nanoparticles to address 1,2-dichloroethane and chlorophenols, some studies have reported that the reaction activation energy against the dechlorination energy barrier has been improved, and reaction conditions such as the temperature of the hydrogen reduction process can be adjusted to a lower level. , Similar to the gas–solid reaction process, the surface acidity of the catalyst is particularly important for the adsorption of target chlorinated organic compounds in a liquid HDC process. The catalytic system using acid zeolite as the carrier seems to have a high reaction rate because its Brønsted acidity shows high selective adsorption for C–Cl bonds, especially for chlorophenol species …”
Section: Application Of Liquid Phase Dechlorinationmentioning
confidence: 99%
“…Although Pd had proven to be the most suitable catalyst for the HDC reaction, the poisoning of active Pd sites by saturation of chloride ions and the trend of aggregation or sintering during long-term dechlorination operation significantly hinder the catalytic activities and stabilities. 17,18 Consequently, the rational design of the catalyst in a HDC reaction remains a great challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Catalysts play a crucial role in HDC reactions. At present, the commonly used catalysts for HDC reactions include Pd, Rh, Pt, Ni, , and Co, among which the Pd-based catalysts are commonly recognized as the most promising one. In addition, the bimetallic Pd-M catalysts (M = Fe, Co, , Ni, Cu, , Au, or Ag ) can enhance the catalytic performance compared to their monometallic counterparts due to the synergistic effect between Pd and M. Moreover, using non-noble metals as the second metal can also decrease the cost of the catalysts.…”
Section: Introductionmentioning
confidence: 99%